Characteristics of Onion Crackers from Soybean Dregs Flour and Mung Bean Flour - Rahmayuni Rahmayuni; Rahyeni Milia Sundari; Raswen Efendi (Jurnal Teknologi Hasil Pertanian, 2025)
Onion crackers are made from tapioca and garlic in addition to wheat flour. Onion crackers have a low nutritional content, so it is necessary to substitute other ingredients to improve the chemical and physical quality of crackers. This study aims to obtain the best ratio between soybean dregs flour and mung bean flour based on the physical, chemical, and sensory properties of onion crackers. The research was conducted experimentally using a completely randomized design (CRD) with five treatments and four replications. The treatments in this study were the ratio of soybean dregs flour and mung bean flour, namely 100:0, 75:25, 50:50, 25:75, and 0:100. Data were statistically analyzed using analysis of variance (ANOVA), followed by Duncan’s multiple range test (DMRT) at 5% level. Parameters observed included moisture content, ash content, protein content, linear expansion, and sensory evaluation. Results of the analysis of variance showed that the substitution of soybean dregs flour and mung bean flour had a significant effect on all parameters. The results showed that the selected treatment was AK2 (ratio of 75% soybean dregs flour and 25% mung bean flour) with a moisture content of 6.43%, an ash content of 4.33%, a protein content of 6.68%, and a linear expansion of 119.50%. Descriptive sensory evaluation of AK2 crackers by panelists obtained a yellowish white color, a slight bean aroma, a soybean taste, crispy, and overall assessment hedonically was favored by panelists.